2002
DOI: 10.1111/1469-8986.3920254
|View full text |Cite
|
Sign up to set email alerts
|

Startle potentiation in aversive anticipation: Evidence for state but not trait effects

Abstract: The present study was undertaken to determine whether aversiveness contributes to startle potentiation in anticipation of affective pictures above and beyond the effects of emotional arousal. Further, participants high in trait anxious apprehension, which is characterized by worry about the future, were expected to show especially pronounced anticipatory startle responses. Startle blink reflex was measured during warning stimuli that predicted the valence of ensuing aversive/unpleasant, pleasant, or neutral pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
34
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 11 publications
9
34
5
Order By: Relevance
“…Importantly, research on other physiological systems demonstrates that worry is not associated with general physiological hyperactivity. Earlier reports have shown that worry is associated with cardiovascular hyporesponsivity to aversive stimuli [Borkovec and Hu, 1990;Borkovec et al, 1993] and normative potentiation of eyeblink startle in anticipation of aversive stimuli [Nitschke et al, 2002] and while viewing them [Larson et al, 2007]. In addition, the present results indicate that corticospinal motor excitability during worry is not at ceiling, based on the finding of smaller mean MEP amplitude than during motor imagery.…”
Section: Discussionsupporting
confidence: 75%
“…Importantly, research on other physiological systems demonstrates that worry is not associated with general physiological hyperactivity. Earlier reports have shown that worry is associated with cardiovascular hyporesponsivity to aversive stimuli [Borkovec and Hu, 1990;Borkovec et al, 1993] and normative potentiation of eyeblink startle in anticipation of aversive stimuli [Nitschke et al, 2002] and while viewing them [Larson et al, 2007]. In addition, the present results indicate that corticospinal motor excitability during worry is not at ceiling, based on the finding of smaller mean MEP amplitude than during motor imagery.…”
Section: Discussionsupporting
confidence: 75%
“…This unpredicted result did not replicate findings reported by prior studies examining the anticipation of emotionally salient, arousing pictures, which have generally found larger blink responses to emotional than to neutral stimuli (Dichter et al, 2002;Lipp et al, 2001;Nitschke et al, 2002;Sabatinelli et al, 2001), or eventually larger responses to unpleasant than to pleasant pictures -interpreted as the affective startle modulation typically found during perception (Allen et al, 1996;Erickson et al, 1995).…”
Section: Discussioncontrasting
confidence: 98%
“…Another important difference compared with preceding studies, suitable of further investigation, concerns the experimental sample. Here participants were unselected female college students, whereas some of previous studies tested those anticipatory effects on male samples with some anxiety disorder, either snake phobic students or participants diagnosed with anxious apprehension (e.g., Nitschke et al, 2002;Sabatinelli et al, 2001). Therefore, it could be interesting to further explore whether the present results during anticipation of emotional picture categories -obtained in a sample of undergraduate women non-selected by means of specific personality traits-might be generalized across gender and replicated in clinical samples, or even with another pleasant or unpleasant picture contents (e.g., thrill scenes, mutilations).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, emotional arousal and emotional influences on attention and perception, which are emphasized in the literature on emotional memory (2-7, 30, 31), are key features of anticipating aversion. Specifically, the anticipation of aversive events is associated with heightened arousal, as indexed by startle (25,(32)(33)(34)(35) and the modulation of perception and attention (36-39) that, in turn, is important for memory encoding (40-42).The present functional MRI (fMRI) study tested whether activation of the amygdala and hippocampus during the anticipation of aversive events is related to subsequent memory of these events. Based on previous findings in our laboratory (24), we expected the dorsal amygdala and anterior hippocampus to be activated both in anticipation of and response to aversive pictures, consistent with the idea that there is one system that governs both processes (26,43).…”
mentioning
confidence: 99%
“…Moreover, emotional arousal and emotional influences on attention and perception, which are emphasized in the literature on emotional memory (2-7, 30, 31), are key features of anticipating aversion. Specifically, the anticipation of aversive events is associated with heightened arousal, as indexed by startle (25,(32)(33)(34)(35) and the modulation of perception and attention (36-39) that, in turn, is important for memory encoding (40-42).…”
mentioning
confidence: 99%